(untitled) (Arquivos do Mudi, 2023)
The COVID-19 pandemic has had a significant impact on global health, with patients experiencing post-infection sequelae such as dyspnea, chronic fatigue, body aches and memory loss. This study aims to investigate the effectiveness of a physical exercise program in improving these symptoms. The database analyzed was from the Clinica e Academia school of physical education at the State University of the Midwest, which receives patients recovering from these symptoms. A structured anamnesis was performed, in which patients reported pre- and post-COVID-19 conditions. Four variables were investigated: dyspnea, chronic fatigue, body aches and memory loss. Training consisted of resistance and aerobic exercises, twice a week, monitored by heart rate and subjective perception of exertion, with workload progressing whenever possible. Each patient received a prescription based on the American College for Prescription of Exercise for Health guidelines. There was a decrease in chronic fatigue (57.1% to 28.6%), dyspnea (50% to 21.4%), body aches (35.7% to 7.1%) and memory loss (35.7% to 28.6%). These findings suggest that the implementation of physical exercises can attenuate post-covid19 symptoms. However, this descriptive study is not conclusive and well-designed essays that can better elucidate the subject are recommended.